Mutation of purD and purF genes further attenuates Brucella abortus strain RB51. (February 2015) - Truong, Quang Lam; Cho, Youngjae; Barate, Abhijit Kashinath; Kim, Suk; Watarai, Masahisa; Hahn, Tae-Wook
Abstract: In the present study, transposon mutagenesis was used to further attenuate Brucella abortus RB51 vaccine strain. Two purD and purF mutants were constructed, characterized and evaluated for attenuation via intracellular survival in murine macrophage-like RAW264.7 and HeLa cells, and by clearance in BALB/c mice. The purD and purF mutants showed significantly decreased intracellular survival, and complementation of these mutants with intact copies of purD or purF genes of RB51 strain was able to restore these defects. In addition, the pur mutants presented significantly lowered persistence in mice. Immunization with purD and purF mutants protected mice against a challenge with the virulent B. abortus strain 544 at a level similar to that of the parent RB51. These data suggest that genes encoding the early stages of purine biosynthesis ( purD and purF ) are required for intracellular survival and virulence of B. abortus . Highlights: Brucella abortus strain RB51 is likely to be virulent toward pregnant cattle and humans. Transposon mutagenesis was used to further attenuate B. abortus strain RB51. Mutants were developed and contained a transposon insertion in purF and purD genes. The purD and purF mutants exhibited significant attenuation in vitro and in vivo. The purD mutant retained protective efficacy similar to that of the RB51 strain.